2006
DOI: 10.1111/j.2006.0030-1299.14850.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographically partitioned spatial synchrony among cyclic moth populations

Abstract: Many species of forest lepidopterans exhibit regular population cycles, which culminate in outbreak densities at approximately ten‐year intervals. Population peaks and mass outbreaks typically occur synchronously and may lead to extensive forest damages over large geographic areas. Here, we report patterns of spatial synchrony among cyclic autumnal moth (Epirrita autumnata) populations across Fennoscandia, as inferred from 24 long‐term (10–33 years) data sets. The study provides the first formal analysis of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 62 publications
2
59
0
Order By: Relevance
“…This also regards previous studies of population dynamics of the two focal geometrid species (e.g. Ims et al 2004;Klemola et al 2006;Tenow et al 2007). Previous studies of impact of parasitoids in these moths have invariably been conducted on relatively small spatial scales, and even such local studies have not proved that larval parasitoids are able to terminate outbreaks (Ruohomäki et al 2000).…”
Section: Discussionmentioning
confidence: 89%
“…This also regards previous studies of population dynamics of the two focal geometrid species (e.g. Ims et al 2004;Klemola et al 2006;Tenow et al 2007). Previous studies of impact of parasitoids in these moths have invariably been conducted on relatively small spatial scales, and even such local studies have not proved that larval parasitoids are able to terminate outbreaks (Ruohomäki et al 2000).…”
Section: Discussionmentioning
confidence: 89%
“…Like most other studies addressing the spatial dimensions of cyclic outbreak dynamics, previous analyses of birch forest moths have focused solely on the issue of regional synchrony across the temporal extent of the study (Klemola et al 2006;Tenow et al 2007), thus without attempting to partition out phase-or scaledependent patterns and processes as we have done here. Nevertheless, the previous studies have concluded that although dispersal could not be ruled out as a contributing synchronizing mechanism (Ims et al 2004), a regionalized climatic Moran effect is more likely.…”
Section: Results (A) General Characteristics Of the Outbreakmentioning
confidence: 99%
“…birch) have recently been highlighted for the insecthost plant system in question (Stenseth & Mysterud 2002;van Asch & Visser 2007;Hagen et al 2008). As phenological patterns are observed to be structured according to latitudinal and altitudinal gradients , as well as topographical features, such a phenological mismatchdriven Moran effect could also be responsible for the more complex spatial dynamics recently reported for birch forest moths (Klemola et al 2006;Tenow et al 2007). Yet, other studies have hinted that dispersal (either in the moths or their enemies) may be important, at least under some circumstances (Ims et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations